Key access and utilization descriptors for sorghum genetic resources - Bioversity International; International Crops Research Institute for the Semi-Arid Tropics; United Sorghum Checkoff Program (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for sorghum utilization.